2016
DOI: 10.1097/md.0000000000005451
|View full text |Cite
|
Sign up to set email alerts
|

VKORC1 and CYP2C9 polymorphisms related to adverse events in case-control cohort of anticoagulated patients

Abstract: Vitamin K antagonists (VKAs) are highly effective but have a narrow therapeutic index and require routine monitoring of the INR. The primary aim of pharmacogenetics (PGx) is to optimize patient care, achieving drug treatments that are personalized according to the genetic profile of each patient. The best-characterized genes involved in VKA PGx involve pharmacokinetics (VKORC1) and pharmacodynamics (CYP2C9) of VKA metabolism. The role of these genes in clinical outcomes (bleeding and thrombosis) during oral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For example, in addition to clinical variables, genetic variation of cytochrome P450 2C9 (a warfarin metabolism enzyme, has also been strongly associated with warfarin-resistant phenotype. 57 The general consistency of our MD-simulation results, along with the cell-based experimental data, not only help us to understand the mechanism of warfarin inhibition of VKOR, but also provide important clues to help explain warfarin-resistant clinical phenotypes and design safer anticoagulant drugs for treating disorders involving vitamin K metabolism.…”
Section: Discussionmentioning
confidence: 58%
“…For example, in addition to clinical variables, genetic variation of cytochrome P450 2C9 (a warfarin metabolism enzyme, has also been strongly associated with warfarin-resistant phenotype. 57 The general consistency of our MD-simulation results, along with the cell-based experimental data, not only help us to understand the mechanism of warfarin inhibition of VKOR, but also provide important clues to help explain warfarin-resistant clinical phenotypes and design safer anticoagulant drugs for treating disorders involving vitamin K metabolism.…”
Section: Discussionmentioning
confidence: 58%
“…They did not find any effect of using genetic algorithms on a reduction in the risk of thromboembolic events 12 . However, one candidate-gene study found that variants in VKORC1 and CYP2C9 were associated with thrombotic events, such as stroke, TIA, and venous thromboembolism, among others 13 . Furthermore, two studies that included patients from the Chinese Han population found that VKORC1 mutations were associated with a higher risk of cardiovascular diseases, including stroke 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…1 , Table 1 ). Further, genetic variation in the VKORC1 gene also predicts warfarin dosing and response 39 . A low activity T allele of rs9923231 in the VKORC1 is very common in East Asians (0.95; EAS) compared to Europeans (0.40; NFE) and South Asians [0.20 (Sikhs and SAS) and 0.19 (GIH)], and was lowest (0.06) in African (YRI).…”
Section: Discussionmentioning
confidence: 99%